Rate‐All‐That‐Apply (RATA) comparison of taste profiles for different sweeteners in black tea, chocolate milk, and natural yogurt. Issue 2 (22nd January 2020) - Tan, Vicki Wei Kee; Wee, May Sui Mei; Tomic, Oliver; Forde, Ciarán G.
Abstract : Abstract: Growing health concerns have increased interest in reducing the consumption of added sugars, which can be achieved by substituting or replacing sugar with sweeteners to maintain sensory intensity and quality. The growing availability of sweeteners has increased the complexity of the perceptual landscape as sweeteners differ in the qualitative, intensity, and temporal properties. A sweetener that can match the perceptual properties of sucrose in different food matrices is likely to have broad applications. In complex foods, sweetness is influenced by the taste interactions with the existing tastants and possible matrix effects that influence release and perception of sweetness. The current study compared the taste properties of three food matrices (black tea, chocolate milk, and natural yogurt) sweetened by sucrose to those sweetened using eight different sweeteners (acesulfame‐K, aspartame, erythritol, luo han guo (Mogroside), palatinose (iso‐maltulose), stevia (Reb‐A), sucralose, and sucrose–allulose mixture) using Rate‐All‐That‐Apply. The sensory properties of each sweetener differed across matrices, with sucrose–allulose mixture, aspartame, erythritol, palatinose, and sucralose having the most similar taste to sucrose across all foods. By contrast, acesulfame‐K, stevia, and luo han guo had taste profiles that most varied from sucrose, characterized by side tastes such as bitterness, chemical taste, and a low sweetness. Sweeteners differed most from sucrose when presented in natural yogurt compared to tea and chocolate milk. A food's taste properties can suppress sweetness intensity and promote undesirable side tastes. Taken together, these findings highlight the importance of testing sweeteners in complex foods and help identify sweeteners and sweetener combinations that can replicate the sweetness of sucrose and support sugar reduction. Practical Application: Food manufacturers and researchers can refer to the results of the sensory profiles to identify suitable sweeteners substitutes for sucrose in foods with similar taste profiles to those tested. The current article highlights important changes to sweetener sensory properties when presented in different complex foods, and provides an indication of the potential for calorie reduction by substituting sucrose with a range of low or no calorie sweeteners.